FACTIBILIDAD TÉCNICA – ECONÓMICA DE UN SISTEMA FOTOVOLTAICO PARA LA GENERACIÓN ELÉCTRICA DEL SECTOR PITAL CANTÓN QUEVEDO - SÁNCHEZ ASPIAZU, JOSUE VICTOR (2025)
This study aims to evaluate the technical and economic feasibility of implementing a photovoltaic system in the Pital sector of the Quevedo canton, Ecuador